Teacher’s Performance to Maintain Students’ Learning Enthusiasm in the Online Learning Condition - Syahranie Wahab; Marwal Iskandar (Universitas Muhammadiyah Barru, 2020)
This study was aimed to investagate teachers’ performance in implementing the guidance treatment to students for maintaing students’ enthusiasm to study in the distance learning condition. As we know that in the covid-19 pandemic situation, the learning system shifted from direct classroom interaction to online distance learning. This suddenly changing system has the potential to reduce student enthusiasm for learning. The current study was a qualitative research conducted by using qualitative descriptive method. In-depth interviews were applied to determine the model of the guidance treatment and performance conducted by an EFL teacher. This research was conducted at SMK Muhammadiyah 1 Sangatta in Kutai Timur Regency, and the research subject was an EFL teacher. The focus of this research was that to examine and obtain data about the supervision toward the teacher. The supervision was conducted by the school principal. For collecting data, the researchers used interview results and documentation. Based on the findings and the analysis, it could be concluded that the implementation of the guidance treatment for students at SMK Muhammadiyah 1 Sangatta had been performed well by teachers. This was evidenced by the results found by researchers in the process of planning, implementation, evaluation, and follow-up action. All of these processes had been carried out very well by the teacher.